Addressing changed sexual functioning in cancer patients: A cross-sectional survey among Dutch oncology nurses. Issue 6 (December 2015) - Krouwel, E.M.; Nicolai, M.P.J.; van Steijn-van Tol, A.Q.M.J.; Putter, H.; Osanto, S.; Pelger, R.C.M.; Elzevier, H.W.
Abstract: Purpose: In most types of cancer, the disease and its treatment can result in altered sexual function (SF). Oncology nurses are strategically placed to address SF since they have frequent patient interaction. Our aim was to establish their knowledge about and attitudes to SF in oncology care and identify their perceived barriers to addressing the subject. Methods: A 37-item questionnaire was administered during the 2012 Dutch Oncology Nursing Congress and mailed to 241 Dutch oncology nursing departments. Results: The majority of 477 nurses (87.6%) agreed that discussing SF is their responsibility. Discussing SF routinely is performed by 33.4% of these nurses, consultations mainly consisted of mentioning treatment side-effects affecting SF (71.3%). There were significant differences depending on experience, knowledge, age, academic degree and department policy. Nurses ≤44 years old (p < 0.001), with <10 years oncology experience (p = 0.001), insufficient knowledge (p < 0.001), no academic degree (p < 0.001), and in whose department policy was lacking or inadequate (p < 0.001), were less comfortable discussing SF. Barriers included lack of training, presence of a third party and no angle or motive for initiating discussion. Conclusions: Findings suggest oncology nurses consider counselling on sexual issues to be an important responsibility, in line with discussing other side-effects caused by the disease or its treatment. Nevertheless, cancer patients may not routinely be receiving a sexual health evaluation by oncology nurses. Results emphasize the potential benefit of providing knowledge, including practical training and a complete department protocol.